Contrasting U–Pb ages from plutons in the Bras d'Or and Mira terranes of Cape Breton Island, Nova Scotia - Barr, S. M.; Dunning, G. R.; Raeside, R. P.; Jamieson, R. A. (Canadian Journal of Earth Sciences, 1990)
U–Pb dates from zircon, titanite, and monazite in plutons of the Bras d'Or and Mira terranes of southern Cape Breton Island, combined with 40 Ar/ 39 Ar and other radiometric age data, indicate that the Bras d'Or and Mira terranes had separate magmatic and metamorphic histories until at least the Middle Cambrian and possibly until the Devonian. The Bras d'Or Terrane is characterized by abundant late Precambrian (ca. 565–555 Ma) dioritic to granitic plutons, as exemplified by the Shunacadie granodiorite ([Formula: see text], U–Pb zircon). Early Ordovician granitic plutons, such as the Kellys Mountain leucogranite with a U–Pb (zircon) age of 498 ± 2 Ma, occur locally. Titanite and 40 Ar/ 39 Ar (hornblende) ages from plutons and metamorphic units suggest that widespread metamorphism may have occurred between these plutonic events and (or) during the Early Ordovician plutonism.Plutons in the Mira Terrane appear to have been emplaced at about 620 Ma or before, as exemplified by the Chisholm Brook granodiorite ([Formula: see text]), and to have been unaffected by younger thermal events, as indicated by close similarity of U–Pb (zircon and titanite) and 40 Ar/ 39 Ar (hornblende) ages. Plutons of Devonian age are localized in an easterly trending belt in the central part of the terrane. In contrast to the Bras d'Or Terrane, widespread latest Precambrian (ca. 565–555 Ma) to Early Ordovician plutonism and metamorphism appear to have been absent. It is unlikely that the Mira and Bras d'Or terranes were juxtaposed before the Early Ordovician.